CRIMINAL LAW POLICY THROUGH THE APPLICATION OF CAPITAL PUNISHMENT ON CORRUPTION IN INDONESIA - ARIANUS HAREFA (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
The handling of corruption crimes is still under the sharp spotlight from various circles, including the public, professionals and law enforcement circles themselves. The various aspects of law enforcement discussed, one of which is the issue of just legal reform, "rule of law" in the sense that the role of higher education of law in improving the quality of law enforcement and moral integrity, having faith and knowledge is highly expected. In order to produce quality and integrity law enforcers, efforts are made, namely the formulation of laws by the legislative body, the application of the law by the courts, and the stage of executing decisions by the Public Prosecutor. Quality law enforcement is carried out through new breakthroughs in the criminal law of corruption, namely by applying the death penalty to perpetrators of corruption in certain circumstances. Under certain circumstances, the death penalty for perpetrators of corruption is considered more effective than imprisonment, deprivation or fines and/or penalties in the form of payment of replacement money. Imposing the death penalty for criminal acts of corruption in Indonesia as referred to in Article 2 paragraph (2) of the PTPK Law (derogate specialist) and in Article 10 of the Criminal Code (generalist derogate) where the act is committed under certain circumstances, then by a judge who adjudicate and decide on the case can be used as a guideline, basis, and reason for the weighting of the criminal against the perpetrator with the aim of providing a deterrent effect and frightening other communities so that the same behavior will not be repeated.